2016
DOI: 10.2319/072316-574.1
|View full text |Cite
|
Sign up to set email alerts
|

Rapid 3D mandibular superimposition for growing patients

Abstract: The rapid superimposition was precise for assessing dentoalveolar changes and structures close to the registration area. However, evaluation of the condyles and ramus area had limitations and needs improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…In cone-beam computed tomography (CBCT) studies, 17,18 voxel-based three-dimensional (3D) superimposition methods were introduced to minimize measurement error, and they were reported as suitable for research in both growing and grown patients. The immediate effects of transverse skeletal and dentoalveolar changes in tooth-borne and bone-borne expenders have already been compared in a previous CBCT study.…”
Section: Introductionmentioning
confidence: 99%
“…In cone-beam computed tomography (CBCT) studies, 17,18 voxel-based three-dimensional (3D) superimposition methods were introduced to minimize measurement error, and they were reported as suitable for research in both growing and grown patients. The immediate effects of transverse skeletal and dentoalveolar changes in tooth-borne and bone-borne expenders have already been compared in a previous CBCT study.…”
Section: Introductionmentioning
confidence: 99%
“…The morphological development of the mandible has been mainly investigated through subjective analysis with the superimposition of 2D images (Björk, ; Solow & Kreiborg, ) or 3D models (Koerich, Weissheimer, de Menezes, & Lindauer, ; Nguyen, Cevidanes, Franchi, Ruellas, & Jackson, ). These studies have provided some information about bone remodeling being a major factor of mandibular development: the mandible changes both in terms of size and global morphology through the activities of osteoblasts and osteoclasts (D. Enlow, ; Nguyen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Ruellas et al [4] suggested superimposing the mandible in growing patients on the mandibular body (mandible without teeth, alveolar bone, rami and condyles) using 3D regional registration. Koerich et al [11] showed that this was a precise method for 3D mandibular superimposition in growing subjects.…”
Section: Discussionmentioning
confidence: 99%